Coupling SAP 2000 with ABC algorithm for truss optimization - Baldissera dos Santos, Rafael; Palomino Tamayo, Jorge Luis (Dyna (Medellín, Colombia), 2020)
In this work, a numerical tool is implemented for size optimization of spatial truss structures. To achieve this goal, the metaheuristic artificial bee colony (ABC) algorithm based on the vivid behavior of honey bees is combined with the commercial software package SAP 2000 via its Application Programming Interface (API). Linking the optimization algorithm to SAP 2000 will allow access to the complete finite element library and potential of the commercial software. In order to do so, the numerical tool is developed within the Excel environment by using macros with the Visual Basic Programming Language. A complete picture is then presented to practitioners of the elaborated numerical tool, which can be used in daily design applications. The correct functionality is demonstrated by means of two challenging practical examples. Extension to other optimization applications can be easily adapted